2022
DOI: 10.18295/squmj.5.2021.075
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence against Infertile Women

Abstract: Domestic violence (DV) against infertile women is an important health concern, which affect their well-being. This systematic review and meta-analysis investigated the prevalence of DV against infertile women. The study was done based on the preferred reporting items for systematic reviews and meta-analysis (PRISMA) on international electronic databases. Inclusion criteria were cross-sectional studies published in English and Persian journals, which investigated the prevalence of DV against infertile women up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A meta-analysis by Sharifi et al 36 revealed that 14-88% of infertile women experienced domestic violence. Nevertheless, we can conclude that knowledge, attitudes, and men's practices regarding male infertility did not necessarily affect a couple's decision on which type of doctor to see or who should get examined first.…”
Section: Item (Couple's Practices) N (%)mentioning
confidence: 99%
“…A meta-analysis by Sharifi et al 36 revealed that 14-88% of infertile women experienced domestic violence. Nevertheless, we can conclude that knowledge, attitudes, and men's practices regarding male infertility did not necessarily affect a couple's decision on which type of doctor to see or who should get examined first.…”
Section: Item (Couple's Practices) N (%)mentioning
confidence: 99%
“…[33][34][35] Women are the most victimized group and experience domestic violence worldwide because of complications related to infertility. 36 Societal beliefs in African communities dictate that it is the responsibility of a woman to raise children. Stigmatization related to not fulfilling this role affects women's mental well-being, and some may also experience gender-based violence 31,37,38 as infertility plays an important role in cases of increased gender-based violence in Africa and other regions.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility not only increases the risk of mental illness, pregnancy complications, and chronic diseases but also increases the risk of offspring developing diseases, such as mental retardation [4][5][6]. Moreover, infertility can cause discrimination, tension in marital relationships, domestic violence and breakdown of marriages [7][8][9]. With the development of science and technology, the accessibility and effectiveness of infertility treatment have improved.…”
Section: Introductionmentioning
confidence: 99%